Digital Marketing: Strategi Efektif dalam Meningkatkan Promosi Usaha Siswa SMKN 2 Pariaman - Sari, Puti Embun; Mariyanti, Eka; Abdilla, Mohammad; Maivalinda, Maivalinda; Sukma, Tri; Vanisya, Winda; Srihasnita, Rita (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Digital marketing activities are an important element in entrepreneurial promotion activities, considering that all forms of activities, especially in the business sector, have gone through the digitalization stage, so that understanding in the digital marketing process must be improved and not to be left behind then goals can continue to be achieved. The use of digital marketing is needed to improve entrepreneurial marketing skills in students of SMK Negeri 2 Pariaman, and students can implement digital marketing and are able to increase their business potential.Digital marketing is an effort to market products with digital media and internet networks, such as Google Business, WhatsApp Business, Instagram, Tiktok, Canva and other platforms. One of the applications of digital marketing in business is the use of Canva. This activity provides guidance on the use of digital marketing with the Canva platform, from designing to utilizing it in student business activities.